Assessing Export Competitiveness and Trade Patterns of Fresh and Chilled Gherkins from India - , Narayan Murigeppa Gunadal, N. M. Kerur, Balachandra K. Naik, Vilas S. Kulkarni, T. R. Shashidhar (Archives of Current Research International, 2024)
India is the largest producer and exporter of fresh and chilled gherkins globally, with significant contributions from Karnataka, Tamil Nadu and Andhra Pradesh, accounting for 25–27 per cent of global exports and generating over $200 million annually. This study analysed the trade direction of Indian fresh and chilled gherkins using secondary data (2011–12 to 2022–23) from APEDA, DGCIS, and other sources. The Nominal Protection Coefficient (NPC) was employed to assess export competitiveness, while the first-order Markov chain approach analysed trade direction. The NPC results indicated that Kuwait was a less competitive market (0.98), Bahrain and Oman were moderately competitive (0.85 each), while the UAE, Qatar, Bhutan and Maldives were highly competitive markets (0.30, 0.27, 0.04 and 0.06, respectively). Bhutan, Qatar and the UAE emerged as the most reliable importers, retaining 100 per cent, 73.95 per cent and 68.69 per cent of their market shares, respectively. The study suggest that the UAE, Qatar, Bhutan and Maldives were the most remunerative markets during the study period. However, the high concentration of exports in a few markets increases trade risks, emphasizing the need for market diversification. Strategic interventions, including pricing alignment and enhanced domestic production promotion, are recommended to boost exports and ensure long-term sustainability.